Study of correlation between age with incidence of endometrial cancer and histopathological type - Bharaswadkar, Ganesh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Endometrial carcinoma is one of the commonest Gynecological malignancy. Endometrioid type is the most common type associated with hyper-estrogenic state and has better prognosis. While non endometrioid type is less common, associated with elderly age and has dismal prognosis. Uterine cancer is most often observed in higher age group with average age at diagnosis of 60 years. It most often occurs in women over 50. 16 cases of endometrial carcinoma were collected from January 2018 until November 2020.The study evaluated the correlation of age with incidence and type of endometrial cancer by categorizing patients into different age groups and then analyzing them. The most affected age group was between 60-70 years and commonest type of endometrial cancer identified was Endometrioid type.